The adequacy of workplace accommodation and the incidence of permanent employment separations after a disabling work injury or illness - Mustard, Cameron A; Orchard, Christa; Dobson, Kathleen G; Carnide, Nancy; Smith, Peter M (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVE ': 'This study aimed to estimate the influence of the adequacy of employer accommodations of health impairments in predicting permanent separation from the employment relationship in a cohort of workers disabled by a work-related injury or illness. ' ' METHODS ': 'The study used data from a retrospective, observational cohort of 1793 Ontario workers who participated in an interviewer-administered survey 18 months following a disabling injury or illness. The relative risks (RR) of a permanent employment separation associated with inadequate employer accommodations were estimated using inverse probability of treatment weights to reduce confounding. ' ' RESULTS ': 'Over the 18-month follow-up, the incidence of permanent separation was 30.1/100, with 49.2% of separations related to health status. Approximately 51% of participants experiencing a separation were exposed to inadequate workplace accommodations, compared to 27% of participants in continuing employment. The propensity score adjusted RR of a health-related separation associated with inadequate accommodation was substantial [RR 2.72; 95% confidence interval (CI) 2.20–3.73], greater than the RR of separations not related to health (RR 1.68; 95% CI 1.38–2.21). ' ' CONCLUSIONS ': 'Incidence of permanent separation in this cohort of Ontario labor force participants was approximately two times more frequent than would be expected. The adequacy of employer accommodation was a strong determinant of the risk of permanent separation. These findings emphasize the potential for strengthened workplace accommodation practices in this setting.
Keywords: cohort study; disability; employment separation; permanent employment separation; work illness; work injury; workplace accommodation